ZnO nanosheets-decorated Bi2WO6 nanolayers as efficient photocatalysts for the removal of toxic environmental pollutants and photoelectrochemical solar water oxidation. (1st July 2020) - Koutavarapu, Ravindranadh; Babu, Bathula; Reddy, Ch Venkata; Reddy, I. Neelakanta; Reddy, Kakarla Raghava; Rao, M.C.; Aminabhavi, Tejraj M.; Cho, Migyung; Kim, Dongseob; Shim, Jaesool
Abstract: Herein we report the fabrication of novel Bi2 WO6 /ZnO heterostructured hybrids for organic contaminant degradation from wastewater and photoelectrochemical (PEC) water splitting upon solar illumination. The Bi2 WO6 /ZnO photocatalysts were synthesized using a simple and eco-friendly hydrothermal process without the support of any surfactants. From the photocatalytic experiments, heterostructured Bi2 WO6 /ZnO nanohybrid catalysts exhibited considerably better photocatalytic performance for rhodamine B (RhB) degradation under solar illumination. The BWZ-20 nanocomposite demonstrated superior photodegradation of RhB dye up to 99% in about 50 min. Furthermore, BWZ-20 photoelectrode showeda lower charge-transfer resistance than other samples prepared, suggesting its suitability for PEC water splitting. The photocurrent densities of Bi2 WO6 /ZnO photoelectrodes were evaluated under the solar irradiation. The BWZ-20 photoelectrode exhibited a significant photocurrent density (0.45 × 10 −3 A/cm 2 ) at +0.3 V vs. Ag/AgCl, which was 1036-times higher than that of pure Bi2 WO6, and 4.8-times greater than the pure ZnO. Such improved photocatalytic and PEC activities are mainly attributed to the formation of an interface between ZnO and Bi2 WO6, superior light absorption ability, low charge-transfer resistance, remarkable production of charge carriers, easy migration of charges, and suppression of the recombination of photogenerated charge carriers. Graphical abstract: Image 1 Highlights: Novel heterostructured ZnO/Bi2 WO6 nanohybrid catalysts were synthesized. Effect of ZnO concentration on photocatalytic and PEC properties are reported. Hybrid photocatalysts have efficiency in complete removal of organic pollutants. The band gap values are reduced as the doping concentration increased. Hybrid photoanodes showed 4.8 times of higher photocurrent density over pure ZnO.